Modified functionally generated path technique to develop occlusal scheme in single complete denture - Anshika Agarwal; Chandana Nair; M K Singhal; Piyush Upadhyay (Wolters Kluwer Medknow Publications, 2019)
Single maxillary denture often represents vigorous challenge to the practicing dentists. The difficulty arises when the maxillary dentures are set to fit the occlusion of natural mandibular teeth. The functionally generated pathway technique registers occlusal pathways of the posterior teeth in functional wax and is described as the "three-dimensional static expression consists of dynamic tooth movement." The current article represents a technique for a patient who was rehabilitated with a maxillary complete denture, and a harmonious occlusion was achieved between the complete denture and the mandibular natural dentition. Functional maxillary denture is therefore in medical dentistry the successful culmination of human's high practice and represents the golden goal sought by every dental practitioner and expected by every denture patient.